Impact Of Mergers & Acquisitions On The Operational Performance And Stability Of Islamic And Conventional Banks - Nazim Ullah
Mergers and acquisitions (M&As) are an alternative way for business expansion and brings benefits for expansion of the market, generation and exploitation economies of scale and scope, gain of market power, proper diversification of products and services and overall improved performance. This study examines the impact of M&As (five years before and five years after) on operational performance and stability for Islamic and conventional banks by taking into consideration the mediating role of market structure. It employs panel data techniques and structural equation modeling (SEM). The study analyses a set of samples consisting of 10 Islamic banks and 14 conventional banks involved in M&As for the period of 2004Q1 to 2020Q4 from six countries which are Qatar, Kuwait, Bahrain, Saudi Arabia, United Arab Emirates, and Pakistan. The Dependent variables: operational performance is estimated using return on assets (ROA), return on equity (ROE) and net interest margin (NIM) while Z-score is used to measure bank stability. Several factors namely bank size, level of bank sizes, intermediary roles (financial and non-financial) and modes of financing are used as independent variables. Moreover, bank specific and macroeconomic variables are used as a control variable. Bank size and the level of bank sizes (i.e., small, medium, and large) are estimated using total assets, total deposits, and operating income. Mediating variables namely Herfindahl-Hirschman Index (HHI) and concentration ratio are used as a proxy for the market structure of the country. The findings imply that the implementation of M&As improves operational performance of Islamic and conventional banks while stability does not show any differences in pre and post M&As. Market structure mediates the relationship of post M&As with operational performance and stability of both types of banks. Moreover, small sized banks imply better impact on the operational performance while large and medium sized banks show better impact on stability of banks. Furthermore, in the pre-M&As scenario, there is no difference between operational performance of Islamic and conventional banks since the sign of the coefficient is the same. In contrary the post M&As scenario, it shows differences between Islamic and conventional banks. Meanwhile, there is no difference of stability in pre and post M&As of Islamic and conventional banks. The implication of the study is twofold. Firstly, M&As have more potential for Islamic banks than conventional banks. Secondly, they should take into consideration the market structure since it mediates the relationship between M&As and operational performance and stability of both types of banks.